Teachers' Beliefs And Practices In Teaching Writing (A Case Study At Assalaam Islamic Boarding School 2015/2016 Academic Year - Hasanah, Ika Mufidatul, Prof. Dr. Endang Fauziati, M. Hum, Mauly Halwat Hikmat, Ph. D (2017)
This study was a case study of English teachers' beliefs and practices at Islamic Senior High School of Assalaam Islamic Boarding School. The objectives were (1) to describe teachers' beliefs and practices in teaching writing, (2) to investigate the practices of teachers' beliefs in classroom practices, (3) to carry out the discrepancy between teachers' beliefs and practices, and (4) to find out the factors contributing in shaping teachers' beliefs and practices in teaching writing. The type of the study was a qualitative study with case study approach. The object of the study was the beliefs of teachers of writing subject at Islamic Senior High School of Assalaam Islamic Boarding School. The subject of the study was the teachers of writing subject at Islamic Senior High School of Assalaam Islamic Boarding School. The data of the study were script of interviews, questionnaire results, field notes, and documents. The techniques of collecting data were through questionnaire, interviews, classroom observations, and documentation. The data validity used was triangulation to gain information through various ways of sources. The techniques of analyzing the data was using Mile's and Huberman's model (1993). The finding of the study showed that, first, the two teachers were consistent with the practices of their beliefs, namely: learning objectives, teaching techniques, learners' roles, and instructional materials. There were discrepancy found in the practices of the beliefs, namely, teaching plan, teaching methodology, classroom procedure, teachers' roles, and assessment. The factors which contribute in discrepancy were class time and students. The factors which contribute in shaping the beliefs and practices of writing teachers at Islamic Senior High School of Assalaam Islamic Boarding School, they are: (1) learning experience (2) teaching experience (3) class time (4) students, and (5) standardized test.